Geospatial Analysis to Identify the Area with High-risk Clusters of Extrapulmonary Tuberculosis in Jambi Municipality, Indonesia - Fairuz Fairuz; Muhammad Syukri; Yuli Puspita Devi; Samsirun Halim (Indian Journal of Public Health)
A significant presence of extrapulmonary tuberculosis (EPTB) cases is estimated in the community in Jambi Municipality, Indonesia, coinciding with the upward trend in TB cases. All EPTB cases from three Jambi hospitals were gathered. Spatial scan cluster analysis was performed using SaTScan 10.1.1 to identify the spatial pattern of EPTB employing the Poisson model. TB patients’ house coordinates were acquired using the Global Positioning System. This study found a cluster of cases in an area centered at −1.574718 S, 103.609117 E with a radius of 4.4 km (relative risk = 4.06). The cluster is found in areas with high population density.